Holy Spirit - Welker, Michael (SysLex, 2026)
"I believe in the Holy Spirit, the holy Christian church, the communion of saints, the forgiveness of sins, the resurrection of the dead and eternal life." This sentence forms the conclusion of the Apostles’ Creed (witnessed since 404), which is prayed in all Western traditions. It has a Trinitarian structure, i.e. it states what is meant by faith in God, the Creator (cf. art. Creation) and Father, in Jesus Christ and in the Holy Spirit. But doesn’t the third article of faith’s talk of the communion of saints, forgiveness of sins, resurrection of the dead and eternal life as an explanation for the Holy Spirit leave many believers rather perplexed? How can we understand the Holy Spirit? The Hebrew and Greek words for spirit (ruach and pneuma) also stand for wind. Like the wind, the spirit "overcomes" people, it " descends". It "takes hold" of both individuals and communities. However, as it is difficult to grasp, it is often regarded as a numinous, incomprehensible divine power. So is it pointless to strive for a clear understanding of God’s spirit? How can we make it clear that God’s Spirit, the Holy Spirit, is a very real power that liberates and uplifts people? He is an unconditionally good spirit and must be distinguished from all kinds of spirits and natural and cultural powers and forces among people. This cannot be achieved through a religiously exaggerated reference to the romance of nature. For even if the divine spirit with its "overcoming" can remind us of a pleasantly warming sun, a cooling wind or a longed-for rain, it must not be confused with natural and cosmic forces.[1] The sun can burn, storms and thunderstorms can destroy and kill. And all natural life inevitably lives at the expense of other life. In what other way can we seek to grasp the unconditionally good spirit of God, the Holy Spirit? Biblical texts and stories can prevent us from getting stuck in our impressions: Forgiveness of sins, the resurrection of the dead - these are just the fanciful speech bubbles of times past. Biblical orientation, especially in the texts of the Old Testament, leads us out of the tangle of ambiguities. [1] Cf. Moltmann, Jürgen, Der Geist des Lebens. Eine ganzheitliche Pneumatologie, Gütersloh 2010. He wants to discover the spirit "in nature, in plants, in animals and in the earth’s ecosystems" (23), "to experience God in all things" (49ff.). [Moltmann, Jürgen, The Spirit of Life. A universal Affirmation, Minneapolis 2001] [2] Cf. Welker, Michael, Der Geist der Freiheit und die Freiheit des Geistes, in: Theologie im Gespräch. Jürgen Moltmann zum 95. Geburtstag, Bad Boll, 22.-24.10.2021, epd-Dokumentation 5, 2022, 7-12.